Substantiation of the pulse method of balancing electrochemical energy storage for transport facilities (Transport systems and technologies, 2019)
The article discusses modern methods of balancing electrochemical energy storage devices on transport facilities and highlights their inherent disadvantages, among which special attention is paid to the duration of the charging and balancing process, which reduces the energy efficiency of both the process itself and the transport facility operation process. A solution to this problem is proposed and theoretically justified by using the pulse method of charging and balancing electrochemical storage. The fundamental difference of the proposed method from the existing ones is shown, which consists in monitoring the parameters of the batteries by the response signal without the use of instrumentation and balancing them by voltage and the amount of stored energy, which increases the reliability and efficiency of the balancing process, and also confirms the appropriateness of using the proposed method.
Keywords: transport facilities, electrochemical energy storage, balancing, pulse method, response signal